Enzyme-Assisted Extraction to Obtain Phenolic-Enriched Wine Lees with Enhanced Bioactivity in Hypertensive Rats - Raúl López-Fer; Maria Margalef; Cristina Torres-Fuentes; Javier Ávila-Román; Gerard Aragonès; Begoña Muguerza; Francisca Isabel Bravo (MDPI AG, 2021)
The antihypertensive effect of the soluble fraction of wine lees (WL) from Cabernet variety grapes was recently reported by our group. This blood pressure (BP)-lowering effect was attributed to the presence of flavanols and anthocyanins. In this context, phenolic-enriched wine lees (PWL) could potentially exhibit a stronger bioactivity. Therefore, the aim of this study was to obtain a soluble fraction of WL with increased phenolic content and evaluate its functionality. The PWL were obtained using an enzyme-assisted extraction based on the hydrolysis of WL proteins with Flavourzyme®. They contained 57.20% more total phenolic compounds than WL, with anthocyanins and flavanols being the largest families present. In addition, PWL also showed greater angiotensin-converting enzyme inhibitory and antioxidant activities. Finally, the antihypertensive activity of the PWL was evaluated in spontaneously hypertensive rats. A single dose of 5 mL/kg body weight of PWL showed a greater BP-lowering effect than the one shown by WL. Moreover, this antihypertensive effect was more prolonged than the one produced by the antihypertensive drug Captopril. These results demonstrate that enzymatic protein hydrolysis is a useful method to maximize the extraction of phenolic compounds from WL and to obtain extracts with enhanced functionalities.